Syntactic Parallelism and Meaning Relation in Tanure Ojaideâ€™s Poetry - Maledo, Richard Oliseyenum (NIU Journal of Humanities; Vol 4 No 4 (2019): KIU Journal of Humanities, Vol. 4 No. 4, December 2019, 2020)
This paper is an analysis of the use of syntactic parallelism as a meaning relation device in the poetry of Tanure Ojaide.  Essentially, the major thrust of Ojaideâ€™s poetry is oil exploration and exploitation and its attendant environmental problems in the Niger Delta region of Nigeria. Eight poems have been selected across four different collections of Ojaideâ€™s poetry for this study. The parallel structures inherent in the poems are identified and analysed following Allenâ€™s (1996) classification of syntactic parallelism to show how syntactic parallelism enables the poet to foreground and organize his eco-critical messages. The study also applies Hallidayâ€™s (1961) â€œScale and Categoryâ€ description of elements of clause structure to handle the structure of the clauses. The findings revealed that the use of syntactic parallelism is functional in written poetry as it enables the poet to foreground the parallel similarity and dissimilarity in the meaning of words and structures which occupy variable positions in the poems. The study further revealed that syntactic parallelism acts as an organising principle in enhancing form and messages in the selected poems of Tanure Ojaide. Keywords : Syntactic Parallelism, meaning relation, oil, exploitation, exploration, poetry, Niger Delta.